The Effect Of Family Planning With ABPK Counseling On Decision Making Family Planning In Wus (Women Of Reproductive Age) - Sabda Nirwana, Betanuari; Khofidhotur Rofiah; Alfika Awatiszahro; Bintang Fathia Sari; Arasyesa Darul Arayan (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
ABPK is a standard guideline for family planning counseling services which not only contains the latest information about contraception or family planning but also contains standard family planning counseling processes and steps that are based on the rights of family planning clients and informed choices. The purpose of this study was to find out whether there was any effect of counseling on family planning using contraceptive collection tools, the sample in this study was total sampling, namely all women of childbearing age in the Grogol area, Kediri district, the method used was providing family planning counseling with assistive devices decision-making. This research is an experimental study, one group pre-test post-test design, conducted in January 2023. The results of the Wilcoxon test, the results of this study are p-value <0.05, from the results of the study it can be stated that there is an effect of family counseling planning with decision-making tools for family planning decision making.